Strangers, Aliens, Foreigners The Politics of Othering from Migrants to Corporations (Volume 106) - Sonnis-Bell, Marissa; Bell, David E.; Ryan, Michelle (Brill, 2018)
To contend with others is to contend with ourselves. The way we "other" others, by identifying and reinforcing social distance, is more a product of who we are and who we want to be than it is about "others." Strangers, Aliens, Foreignersquestions such consolidation and polarization of identities in representations ranging from migrants and refugees, to terrorist labels, to constructions of the local. Inclusive and exclusive identities are observed through often arbitrary yet strategically ambiguous lines of class, religion, race, ethnicity, nationality, social status, and geography. However, despite any arbitrariness in definition, there are very real consequences for the emotional, physical, and psychological well-being of those constructed as "the other", as well as legal governance implications involving human rights and wider sociopolitical ethics. From practical, professional, and political-philosophical points of view, this collection examines what it means to be, or to construct, the Strangers, Aliens, Foreigners. Contributors are David Elijah Bell, Adina Camenisch, Hanna Jagtenberg, Seraina Müller, Lana Pavić, Michelle Ryan, Marissa Sonnis-Bell and Tomasso Trilló.